Subfamilial affiliation of Neoscirula (Acari: Prostigmata: Cunaxidae) and descriptions of three new species of this genus from Brazil - Den Heyer, Jacob; De Castro, Tatiane Marie Martins Gomes [UNESP] (My University, 2008)
The original affiliation of the genus Neoscirula Den Heyer to the subfamily Coleoscirinae Den Heyer, 1979 is maintained. Three new species of this genus are described and illustrated, viz. N. flechtmanni sp. nov., N. oliveirai sp. nov. and N. queirozi sp. nov.. A key to the Brazilian and South African species is provided. Copyright © 2008 Magnolia Press.
Keywords: Bdelloidea; Coleoscirinae; Identification key; Neotropical; Taxonomy